(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
Family and civil legislation indicate that children are also full participants in these relations. Unlike adult children, the procedure for exercising their rights and freedoms by minors is carried out based on their legal status. These norms also cover relations related to the child’s place of residence. While the child’s personal non-property rights serve as a guarantee of his normal development, one of the rights affecting his physical and mental healthy development is the right to his place of residence.